Christian Francken és Sárközi Bálint: A radikális protestantizmus és a kripto-kálvinizmus viszonyához egy 1589-es heidelbergi nyomtatvány alapján - Simon, József (Studia Litteraria, 2026)
In 1589, the Calvinist Franciscus Junius published Christian Francken’s Argumenta XXII in Heidelberg for polemic purposes. The paper attempts to clarify the circumstances under which the manuscript of Francken’s work, probably written in Hungary, was transmitted to the Heidelberg theologian. A new philological data strongly suggests that Bálint Sárközi, an alumnus of Zsigmond Rákóczi, played a crucial role in this mediation. Sárközi’s person, a Calvinist with an exceptional philosophical education, enables us to raise certain questions about the philosophical orientation of Calvinist as well as radical Protestant authors in the Late Renaissance period of Hungary.